Student Interest in Traditional Sports in the Era of Society 5.0 - Ahmad Al Munawar; Diego Gunawan Girsang; Dimas Sugiarto; Delima Lestari Sitorus; Devira Devira; Muhammad Ali Syahbana; Dipa Pangestu; S. Ahmad Habibi (Pusdikra-Publishing.com, 2024)
Given the strong connection between physical activities, such as sports, and factors like quality of life, health, and overall well-being, it is crucial for every person to cultivate an interest in sports. Many sports that are popular throughout the community are categorised as